Criptografia Bioinspirada para IoT: Um Estudo Comparativo de Algoritmos Baseados em DNA - Sales, Mikael M. F.; Aguiar Junior, J. C.; Sousa, A. Wictor Pereira de; Gomes, João Marcelo; Tomaz, Emerson B.; Matos, Filipe de (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the Web, 2025)
Data security in Internet of Things (IoT) devices is a critical challenge due to their inherent limitations in memory, energy, and processing capacity. Traditional security mechanisms are often unfeasible, driving the search for lightweight cryptographic algorithms. In this context, DNA-based cryptography stands out as a promising bioinspired approach. This study presents an empirical and direct comparison of four DNA-based cryptographic algorithms, implemented on a real resource-constrained IoT device, the ESP8266. The analysis quantified performance and efficiency in both encryption and decryption modes, using instrumented measurements of energy consumption (mJ), execution time (𝜇s), electric current (mA), and RAM usage (B). The results reveal statistically significant differences among the algorithms, confirmed by Shapiro-Wilk and Wilcoxon tests. Alg_3 demonstrated the highest efficiency in time and energy, being the fastest and with the lowest total energy consumption, although it required the most RAM. The research highlights the potential of bioinspired cryptography and reinforces the importance of considering the constraints of the target environment when selecting a cryptographic scheme.